Cardiovascular diseases and ischemic stroke: the importance of embolism and thrombosis - Mohammadreza Amirinikpour; Ali Zolfi-Gol; Surena Nazarbaghi; Arash Mosarrezaii; Fatemeh Hamzeh; Zafar Gholinejad (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Congestive heart failure (CHF) is a risk factor for acute ischemic stroke (AIS) incidence. Currently, no specific biomarker exists to differentiate thrombotic and embolic strokes. Managing and treating AIS patients with CHF, particularly those with embolic or thrombotic causes, requires a nuanced understanding of CHF’s role in AIS. Materials & Methods: In this study, we reevaluated the medical records of patients admitted to Urmia Imam Khomeini Hospital from 2006 to 2023. The data was entered into SPSS IBM 23 and evaluated statistically. The exclusion criterion was incomplete medical records. Results: Our results showed that the mean age of AIS patients with and without CHF was 71.18 ± 13.00 and 66.22 ± 14.76 years, respectively (p = 0.001). Hemoglobin levels, lymphocyte and neutrophil counts, and white blood cell counts showed a statistically significant difference between AIS patients with and without CHF. The frequency of thrombotic strokes was twice than that of embolic strokes, with the mean ages 68.75 ± 13.00 and 64.76 ± 16.38 years, respectively (p < 0.001). Patients with atrial fibrillation had an 8.27-fold increased risk of embolic ischemic stroke compared to those without atrial fibrillation (p < 0.001). Blood glucose, red blood cell count, total cholesterol, and LDLc cholesterol showed significant differences between embolic and thrombotic ischemic stroke patients. Conclusion: In conclusion, the findings show that CHF is a risk factor for AIS that acts independently of gender. Monitoring immunological processes may be more clinically significant than RBC count and HCT levels in AIS patients with CHF. Additionally, age, RBC count, anemia, cholesterol, lipoproteins, and blood glucose levels could be used in clinical settings for the differential diagnosis of thrombotic versus embolic ischemic stroke.